Congenital harlequin ichthyosis: A rare case report and literature review - Kawilarang, Bertha (Indian Journal of Case Reports, 2020)
Harlequin ichthyosis is an extremely rare congenital genetic disorder. One of the most prominent features is the severe thickening and scales of newborn skin covering the whole body surface. Here, we report the case of a 31-year-old woman admitted to the maternity emergency unit due to labor pains, with no remarkable history or previous ultrasound examination. A baby boy was born with typical findings of harlequin ichthyosis and clinical diagnosis was made. Despite treatment, the newborn died on the third day. The purpose of this report is to share our experience in managing this rare case and to increase awareness of the severity of the disease.